2017
DOI: 10.1080/09540105.2017.1406459
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C supplementation improved the efficacy of foot-and-mouth disease vaccine

Abstract: Vitamin C (VC) is an essential micronutrient and plays important roles in various biological processes including immune responses. Vaccination can stimulate immune responses effectively for prevention of virual infection. Adequate VC intake is required for the immune system to function efficiently. In this study, we evaluated the biological function of VC on immune response to inactivated foot-and-mouth disease (FMD) vaccine. The C57BL/6 mice were injected intraperitoneally with different dose of VC daily foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…We further investigated the effect of L-EPS as the adjuvant on enhancement of antibody responses of foot-and-mouth disease (FMD) vaccine in a mouse model. FMD is a highly contagious and economically important disease of cloven-hoofed livestock (Wu et al, 2017). Studies showed that humoral immune responses are important in protection against FMD (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further investigated the effect of L-EPS as the adjuvant on enhancement of antibody responses of foot-and-mouth disease (FMD) vaccine in a mouse model. FMD is a highly contagious and economically important disease of cloven-hoofed livestock (Wu et al, 2017). Studies showed that humoral immune responses are important in protection against FMD (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination has been proved to be the most cost-effective strategy for controlling a wide variety of infectious diseases (Wu, He, & Kang, 2017;Zhang et al, 2018). Various approaches have been developed recently in order to improve vaccine potency, particularly with the respect to choose of a better adjuvant.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies revealed that vitamin C has immunomodulatory functions (4,8,19,22,23). Vitamin C supplementation to animals enhanced phagocytosis of macrophages and proliferated helper T cells and B cells (4,8).…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C, also known as L-ascorbic acid, is a water-soluble vitamin [92]. Several investigations indicated that vitamin C is an essential factor for the anti-viral immune responses through increasing production of anti-viral cytokine, interferon (IFN)-α/β especially against influenza A virus (H3N2) at the early time of infection [93], [94]. Similarly, in another animal study, vitamin C deficiency increased the lung pathology of influenza virus-infected gulo-/-mice.…”
Section: Vitamin Cmentioning
confidence: 99%